Effects of Soy-Germ Protein on Catalase Activity of Plasma and Erythocyte of Metabolic Syndrome Women - HERY WINARSI; SIWI PRAMATAMA MARS WIJAYANTI; NURTJAHJO DWI SASONGKO; AGUS PURWANTO (Bogor Agricultural University, Indonesia, 2015)
Oxidative stress always accompany patients with metabolic syndrome (MS). Several researchers reported that soy-protein is able to decrease oxidative stress level. However, there is no report so far about soy-germ protein in relation to its potential to the decrease oxidative stress level of MS patients. The aim of this study was to explore the potential of soy-germ protein on activity of catalase enzyme in blood’s plasma as well as erythrocytes of MS patients. Double-blind randomized clinical trial was used as an experimental study. Thirty respondents were included in this study with MS, normal level blood sugar, low-HDL cholesterol but high in triglyceride, 40-65 years old, Body Mass Index > 25 kg/m2, live in Purwokerto and agreed to sign the informed consent. They were randomly grouped into 3 different groups, 10 each: Group I, was given special milk that contains soy-germ protein and Zn; Group II, soy-germ protein, while Group III was placebo; for two consecutive months. Data were taken from blood samples in 3 different periods i.e. 0, 1, and 2 months after treatment. Two months after treatment, there was an increase from 5.36 to 20.17 IU/mg (P = 0.028) in activity of catalase enzyme in blood’s plasma respondents who consumed milk containing soy-germ protein with or without Zn. A similar trend of catalase activity, but at a lower level, was also noticed in erythrocyte; which increased from 88.31 to 201.11 IU/mg (P = 0.013). The increase in activity of catalase enzyme in blood’s plasma was 2.2 times higher than that in erythrocytes.